Audit Partner Assignments and Audit Quality in the United States - Lee, Hye Seung (Grace); Nagy, Albert L.; Zimmerman, Aleksandra B. (The Accounting Review, 2019)
ABSTRACT This paper examines the demand- and supply-side factors associated with audit partner selection and assignment in the United States. First, we examine whether audit partner gender and experience are associated with board and management gender and experience. Second, we investigate whether engagement audit quality varies with audit partner gender and experience, controlling for selection effects. The results indicate that companies with more gender-diverse boards of directors and top management teams are more likely to have a female lead audit partner. In addition, the experience of the client's board is positively associated with the experience of the lead audit partner. In terms of audit quality, we find that higher audit fees are positively associated with female and more experienced audit partners. Our results shed light on the important role that partner characteristics play in the demand and supply sides of audit quality.